Pengaruh Layanan Bimbingan Klasikal Terhadap Kedisiplinan Belajar - Lestari, Kiki Rizki Indah; Subardi, Subardi (Program Studi Bimbingan dan Konseling Pendidikan Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
ABSTRACT Classical service guidance is very important for students especially in helping to provide understanding to students so as not to do learning indiscipline. This is consistent with the purpose of the service classical guidance, which aims to help students to have understanding of himself and being able to develop skills for identify responsibilities or sets of behaviors that are appropriate for adjustment to the environment, and able to overcome the problem Alone. The purpose of this study is to determine the effect of service classical guidance on student learning discipline in SMA Negeri 1 Jebus. This research uses descriptive quantitative research. Technique data collection used in this study is a questionnaire (questionnaire) and documentation. While the data analysis technique used is analysis simple linear regression and the sample in this study totaled 35 participants educate. The results obtained from the study of the influence of classical guidance services on the learning discipline of students at SMA Negeri 1 Jebus shows that there is an influence of classical guidance services on discipline learn students. Great influence of classical services on discipline student learning by 28.8%. This is shown by the research results obtained significant value is 0.001 and the probability value in this study is 0.05. If the value sig0.001<0.05, then it can be stated that Ha is accepted and Ho is rejected. Decision making can also be done with Ttable values ​​with Tcount. It can be seen that Tcount > Ttable. So from these results you can concluded that there is an influence of classical guidance services on student learning discipline of 28.8%.